(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction: There exists a complex interaction between human immunodeficiency virus (HIV), infection and immune function, with a dominant effect of HIV infection on nutritional status. The influence of nutrition on immune function generally shows that suboptimal nutrition results in immunological deficiencies. Nutrient deficiencies cause immune suppression and increase susceptibility to infections with a resultant loss of immune cell function which allows intrusion by several different infectious agents. The result is reduction of the ability of the body to fight disease and subsequent acquisition of opportunistic infections. Nutrients that play a big role in immune function include protein, total energy, lipids, amino acids, vitamins, and minerals. Optional nutrition alters immunological function and therefore disease states. This interaction affects the body’s immune status predisposing one to infections. Proteins play roles as structural components of tissues and also antibodies, cytokines, acute-phase proteins, components of the complement pathways, transcription factors and enzymes. Deficiency of protein could lead to immunologically important changes in enzyme-dependent activation, antioxidant protection, complement activation, antibody- mediated virus neutralization and intercellular communication via cytokines. Therefore the study was carried out with the aim of exploring the nutrition interventional effect of the patients suffering from HIV/AIDS at a care center in India. Material and Methods: The present study comprised of 30 HIV positive cases (age 20 - 60 years, both male and female) who were admitted to the institution. They were provided with a standard regular nutrition guide and followed up with their CD4 count post intervention; till their discharge from the sanatorium. Patients were explained the process of the study. A written informed consent was taken from all the patients. A diet chart was prepared based on their health condition. Balanced diet rich in protein (ragi malt) and immune boosters (like wheat grass juice, citrus juice, honey, coconut milk and seasonal fruits) were provided to the patients. The patients were advised to follow the daily regimen. If any deterioration was reported, the patient was taken out of the study. The entire schedule was followed strictly for a period of minimum 3 months (to check the changes in CD4 count). Pre and post intervention changes in baseline and the CD4 count was noted. Pre and post intervention of BMI was done by using the Chi square test; to evaluate the changes in number of people in the different categories. Mean weight was compared using either the paired t-test. SPSS (22.0) (IBM Analytics, New York, U.S.A) was used for carrying out the statistical analysis. Results: Their mean duration of stay was 94.13±3.49 days at the sanatorium (range- 90-105days). The overall mean age of the participants was 37.4±10.64. There was no significant difference between the mean ages of the male and the female participants in this study. There was a significant rise in the weight from 40.34kg to 44.5 kg post intervention. When the overall BMI was compared for post intervention changes; the difference was not found to be statistically significant; even though values were slightly increased. There was a significant increase in the CD4 scores in post intervention among the study participants from 315.87 to 485.63 (p=00000001).There was also a mean increase in the weight of the participants post our intervention. Conclusion: It could be concluded that healthy diet regimen has found to be beneficial, since the increased pattern of CD4 scores and weight gain was observed among the patients. Thus, it is a preliminary study; the duration should be increased up to some extent in order to study the role of nutritious food and its mechanism of action in immune suppressed patients.